The Application of Flash Card Media in Improving Arabic Vocabulary in Early Childhood - Ahmad Saefulloh; Titik Rokayani; Windasari Warih (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2026)
Learning Arabic for early childhood requires an approach that suits the characteristics of their cognitive development, especially in vocabulary mastery. Children tend to easily understand and remember language through visual stimuli and enjoyable learning experiences. This study aims to analyze the effectiveness of implementing Flash Card media in improving Arabic vocabulary mastery in children. The research method used is Library Research by reviewing relevant national and international journal articles in the last 5–10 years. Data were collected through academic database searches and analyzed qualitatively by comparing the main findings from various studies. The results of the study indicate that Flash Card media is effective in improving children's memory, understanding, and motivation to learn Arabic vocabulary. This effectiveness is supported by the visual character of the media, repetition, and the application of interactive and enjoyable learning methods. Thus, Flash Card media can be used as an alternative, innovative and applicable learning media in learning Arabic for early childhood.